2021
DOI: 10.3390/plants10102144
|View full text |Cite
|
Sign up to set email alerts
|

High Phenotypic Plasticity in a Prominent Plant Invader along Altitudinal and Temperature Gradients

Abstract: Studies on plant growth and trait variation along environmental gradients can provide important information for identifying drivers of plant invasions and for deriving management strategies. We used seeds of the annual plant invader Ambrosia artemisiifolia L. (common ragweed) collected from an agricultural site in Northern Italy (226 m. a.s.l; Mean Annual Air Temperature: 12.9 °C; precipitations: 930 mm) to determine variation in growth trajectories and plant traits when grown along a 1000-m altitudinal gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The adaptation of plant species to colder environment is believed to be due to phenotypic plasticity or adaptive evolution [7,8]. Phenotypic plasticity allows plants to adapt to the new specific environment [9][10][11][12][13] and it is an underexplored topic, although its understanding is crucial for predicting plant behavior in future climatic scenarios [13][14][15][16]. Comprehensive information on longitudinal patterns of morphological trait variation is very meaningful for exploring morphological diversity and evolutionary trends [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of plant species to colder environment is believed to be due to phenotypic plasticity or adaptive evolution [7,8]. Phenotypic plasticity allows plants to adapt to the new specific environment [9][10][11][12][13] and it is an underexplored topic, although its understanding is crucial for predicting plant behavior in future climatic scenarios [13][14][15][16]. Comprehensive information on longitudinal patterns of morphological trait variation is very meaningful for exploring morphological diversity and evolutionary trends [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, under stressful conditions, clonal plants tend to increase internode length and have longer leaves (van Kleunen et al, 2000), enabling more efficient foraging. Given the diverse habitats frequently encountered by introduced plants as they expand their range, and that plasticity can facilitate adaptation by providing a short-term rapid response to new environments (Fox et al, 2019;Radersma et al, 2020), it would seem that adaptive plasticity should contribute to the success of invasive alien plants (Baker, 1965;Geng et al, 2007;Gentili et al, 2021;Pichancourt & Van Klinken, 2012), at least in the short term (Fox et al, 2019;Radersma et al, 2020). However, this is not necessarily the case (Eriksson & Rafajlović, 2022).…”
mentioning
confidence: 99%
“…Alpine plants usually face rapidly changing environmental conditions in terms of solar radiation, atmospheric pressure, temperature and showing regional morphological variation patterns (Aubin‐Horth & Renn, 2009). Plants cope with resource deficit by allocating biomass between vegetative growth and reproductive growth along increasing elevation to adapt to stressful environments (Gentili et al, 2021). Consistent with previous studies, our study revealed considerable morphological variation in terms of plant height, leaf shape and flower number in M. himalaica .…”
Section: Discussionmentioning
confidence: 99%
“…Faced with sudden climate changes, species with expansive plasticity may persist in new or stressful environments across different conditions (Bakhtiari et al, 2019). Plants at higher elevations usually allocate resources by trading off vegetative and reproductive growth; transplanting and physiological experiments along the elevations are mainly employed to explore the magnitude of phenotypic plasticity (Gentili et al, 2021). Remarkable variation has been observed in plant size, leaf area, flower/seed size and sexual selection responding to precipitation or temperature change in alpine plants (Aubin‐Horth & Renn, 2009; de Villemereuil & Gaggiotti, 2015; Lopez‐Goldar & Agrawal, 2021).…”
Section: Introductionmentioning
confidence: 99%